2017
DOI: 10.1002/joc.5382
|View full text |Cite
|
Sign up to set email alerts
|

Improved seasonal prediction of UK regional precipitation using atmospheric circulation

Abstract: The aim of this study is to further our understanding of whether skilful seasonal forecasts of the large‐scale atmospheric circulation can be downscaled to provide skilful seasonal forecasts of regional precipitation. A simple multiple linear regression model is developed to describe winter precipitation variability in nine UK regions. The model for each region is a linear combination of two mean sea‐level pressure (MSLP)‐based indices which are derived from the MSLP correlation patterns for precipitation in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 36 publications
3
37
2
Order By: Relevance
“…But such a skill is actually "concentrated" in the first few days, because the trajectories tend to converge to the climatology after 20 days. The combination of several skill scores shows that such a system is not appropriate for ensemble forecasts beyond lead times of 40 days, which is lower than what is reported by Baker et al (2018) for a meteorological forecast of the NAO. Although the forecast system is random, it contains elements of the dynamics of the atmosphere, from the choice of The diamonds indicate the reliability of CRPS (on the same scale as CRPSS).…”
Section: Discussioncontrasting
confidence: 61%
“…But such a skill is actually "concentrated" in the first few days, because the trajectories tend to converge to the climatology after 20 days. The combination of several skill scores shows that such a system is not appropriate for ensemble forecasts beyond lead times of 40 days, which is lower than what is reported by Baker et al (2018) for a meteorological forecast of the NAO. Although the forecast system is random, it contains elements of the dynamics of the atmosphere, from the choice of The diamonds indicate the reliability of CRPS (on the same scale as CRPSS).…”
Section: Discussioncontrasting
confidence: 61%
“…GloSea5, has significant skill (correlation 0.62) for the wintertime NAO at 2-to 4-month lead times for a 20-year period (1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011). The GloSea5 forecasts have since been used for applications such as seasonal forecasts of regional UK precipitation (Baker et al, 2017), weather-related impacts on UK transport (Palin et al, 2016), Baltic Sea ice (Karpechko et al, 2015), and UK energy demand and supply (Clark et al, 2017). Athanasiadis et al (2017) showed that even higher skill (correlations of 0.85) can be obtained for the NAO using a multimodel ensemble (MME) of three seasonal forecast systems (GloSea5, NCEP-CFSv2, and CMCC) but found that the exact level of skill was sensitive to both the hindcast period and the NAO definition used.…”
Section: 1029/2018gl078838mentioning
confidence: 99%
“…This might suggest that extreme central European rainfall winters are poorly predicted by GloSea5. However, there are hints of predictability for other patterns (Baker et al, ) and winter 2016/2017 is an extreme case to further investigate this.…”
Section: Circulation Patterns Associated With European Rainfall and Tmentioning
confidence: 99%